SANAD AND ULAMA NETWORK OF THE QURANIC STUDIES IN NUSANTARA - Bizawie, Zainul Milal (Center for Research and Development of Religious Literature and Heritage, 2015)
In several studies related to the development of Qur'anic studies, especially in the field of interpretation, implicit questions remain unanswered on current connectivity and the authority of science in the Qur'anic studies as well as the capability of a person in compiling commentary or interpretation of the Qur?an that has an effect on Islamic society in Indonesia. Interpretations of al Quran today seems to be affected by various sources leading to polemics. According to scholars in Nusantara, it can be understood that there is a connection with the network of scholars based in the Middle East making the thoughts unseparated from the cleric network. Therefore, to uncover a network of sciences and chain of transmission lines (sanad) in Qur'anic studies is very important, particualrly in understanding the intersection between Huffaz clerics and tarekats in the dissemination of teaching the Qur'an.The study highlights that there is continuity and correlation between Huffaz and tarekat scholars network in Nusantara. However, at this time, the development of interpretation studies in Nusantara seems to be increasingly departed and separated by the guards of Qur?an, tarekat and the Islam community.